Antecedents of Organizational Citizenship Behavior Analysis and its Impact Toward Organizational Effectiveness on A Fruit Ice Cream Manufacture - Gunawan, Annetta; Natalia, Natalia (Journal the Winners: Economics, Business, Management, and Information System Journal, 2012)
To achieve organizational effectiveness, every company needs not only qualified human resources, but also employees who perform organizational citizenship behavior (OCB), which is influenced by individual internal factor i.e. big five personality and its external factor i.e. job satisfaction and organizational commitment. PT Harapan Surya Lestari also needs employees with high OCB level to maintain the sustainability of the company. The purpose of this research is to analyse the effects of big five personality, job satisfaction, and organizational commitment of the employees to organizational citizenship behavior and its impact toward organizational effectiveness on PT Harapan Surya Lestari (HSL). The method used in the research is Path Analysis. The data is obtained from questionnaire disseminated to all the employees of PT HSL in order to measure the level of big five personality, job satisfaction, and organizational commitment of the employees and organizational effectiveness from the perception of each employee, using likert scale. Results from the data analysis obtained structural equations Y = 0,240 X1 + 0,166 X2 + 0,502 X3 + 0,6671 Îµ1 Â where simultaneously big five personality, job satisfaction, and organizational commitment contribute significantly to organizational citizenship behavior of 55,5% and Z = 0,461 X2 + 0,374 Y + 0,6921 Îµ2 Â where simultaneously job satisfaction and organizational commitment contribute significantly to organizational effectiveness of 52,1%.